Applying an environmental public health lens to the industrialization of food animal production in ten low- and middle-income countries - Yukyan Lam; Jillian P. Fry; Keeve E. Nachman (BMC, 2019)
Abstract Background Industrial food animal production (IFAP) is characterized by dense animal housing, high throughput, specialization, vertical integration, and corporate consolidation. Research in high-income countries has documented impacts on public health, the environment, and animal welfare. IFAP is proliferating in some low- and middle-income countries (LMICs), where increased consumption of animal-source foods has occurred alongside rising incomes and efforts to address undernutrition. However, in these countries IFAP's negative externalities could be amplified by inadequate infrastructure and resources to document issues and implement controls. Methods Using UN FAOSTAT data, we selected ten LMICs where food animal production is expanding and assessed patterns of IFAP growth. We conducted a mixed methods review to explore factors affecting growth, evidence of impacts, and information gaps; we searched several databases for sources in English, Spanish, and Portuguese. Data were extracted from 450+ sources, comprising peer-reviewed literature, government documents, NGO reports, and news articles. Results In the selected LMICs, not only has livestock production increased, but the nature of expansion appears to have involved industrialized methods, to varying extents based on species and location. Expansion was promoted in some countries by explicit government policies. Animal densities, corporate structure, and pharmaceutical reliance in some areas mirrored conditions found in high-income countries. There were many reported weaknesses in regulation and capacity for enforcement surrounding production and animal welfare. Global trade increasingly influences movement of and access to inputs such as feed. There was a nascent, compelling body of scientific literature documenting IFAP's negative environmental and public health externalities in some countries. Conclusions LMICs may be attracted to IFAP for economic development and food security, as well as the potential for increasing access to animal-source foods and the role these foods can play in alleviating undernutrition. IFAP, however, is resource intensive. Industrialized production methods likely result in serious negative public health, environmental, and animal welfare impacts in LMICs. To our knowledge, this is the first systematic effort to assess IFAP trends through an environmental public health lens for a relatively large group of LMICs. It contributes to the literature by outlining urgent research priorities aimed at informing national and international decisions about the future of food animal production and efforts to tackle global undernutrition.